PRACTICAL ASPECTS OF THE TRADITIONAL TYPES OF THERMAL STRENGTHENING OF BIGVOLUME SLUGS OF TWO-PHASE TITANIUM ALLOYS - V. N. Fedulov (Литьë и металлургия)
Practical possibilities of variation of the thermal processing parameters at receiving of fixed level of alloy BT23 hardening in large slugs are considered.